(3bUjOI (B"(3HGfJ SYGO(B"s - (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHj Gdjhe eJHhd eJje EKQgG de ojaO ecHhd s
(3BNQgG (B:s
(3jGQH Ud Ydi GdgOi hTjYJI hSdef OGFeoG PG GdaVd eCehd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B481 - (3U(B484s
(3HgG fXGe GdJYbjHIs
(3hQO CjVG JMJ Qbe (B2185(3, (B2187 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B110 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1329s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs